Evaluasi Penanganan Ruas Jalan Nasional: Studi Kasus: Jalan Nasional di Wilayah Kerja Satker P2JN Provinsi Kepulauan Bangka Belitung - Budiarto, AHMAD ARIEF TEGUH ([Yogyakarta] : Universitas Gadjah Mada, 2015)
Maintenance of roads in ministerial of public work regulation’snumber 13/PRT/M/2011 regarding the procedures for maintenance and road overseer stated pattern of road maintenance should always be done by considering the effectiveness and efficiency, which is the type of maintenance on a road section shall be in accordance with the existing road conditions and available funds. The funds raised for the handling National Highway in Bangka Belitung Islands annually increased. As the amount of funds for the handling of national roads in the province of Bangka Belitung it is important to do an evaluation of the effectiveness and efficiency of road maintenance programming starting from 2012 up to 2014. The study begins by identifying the level of road maintenance needed of each segment in each of the national roads in the province of Bangka Belitung years of 2012- 2014 based on the pavement condition that based on number of LHR and IRI and also traffic conditions that based on the value of V/C ratio. The next process is to compare the level of needs with the level of realization is done used the model of the effectiveness of the handling that modified model of IPA (Importance Performance Analysis), which an outlined the problem into 4 (four) quadrant is quadrant-I (handling needs to be improved), quadrant-II (road handling effective), quadrant-III (excessive road handling wasteful); quadrant-IV (low needs and addressed as needed so effectively), so quadrant I and quadrant III are needed seriouslyattentions. The results of the analysis of an effectiveness for the handling an each national roads in the province of Bangka Belitung in 2012 along the 0.04% (0.2 miles) long national roads included in the quadrant-I (handling needs improvement) and 16.6% (92.454 km) long road national are in quadrant III (handling of this wasteful). In 2013 there was no road into that way is in the quadrant-I, while roads that are in quadrant III is 16.1% (89.418 km) length of national roads. In 2014 road into that way’s the quadrant-I of path length of 0.04% (0.2 miles) long national road. While entering the quadrant-III are all 4.3% (23.659 km) length of national roads. In 2012,deviations in quadrant-I was dealt with the reconstruction needs regular maintenance and periodic maintenance needs in 2014 dealt with routine maintenance. Deviations in quadrant III needs a routine maintenance for handled by widening and routine maintenance with regular maintenance.